A nonverbal signal of trustworthiness: An evolutionarily relevant model. Issue 2 (2nd July 2020) - Wood, Andy
ABSTRACT: This study introduces and provides evidence of an Evolutionarily Stable Signalling (ESS) System in the buyer-seller context through three experiments. An ESS system is one where a signaller (in this study, the seller) conveys positive intent to the receiver (customers) in a reliable manner that leads to the buyer's benefits. This study uses the 'felt' or genuine smile of salespeople as a reliable signal. The non-consciously generated genuine smile of a salesperson leads to positive, trustworthy assessments by buyers. Buyers reach their conclusions about the trustworthiness of the salesperson rapidly and often without conscious evaluations. These studies simultaneously capture the response time and the cognitive assessments of the subjects. Their decision on the trustworthiness of the salesperson likely provides the foundation for subsequent cooperative exchanges. Using both response time and cognitive assessments allows these series of experiments to develop evidence of this ESS system in the present day.